PENGARUH ETOS KERJA, DISIPLIN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS KETENAGAKERJAAN DI KABUPATEN SITUBONDO - Aryudha, Fernandi; Wahyuni, Ika; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this research is to analyze and test the influence of work ethic, work discipline and leadership on employee performance through job satisfaction. The sampling technique is determined by Non-Probability Sampling using Total Sampling or saturated samples. Data analysis and hypothesis testing in this research used the Structural Equation Model - Patial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that work ethic and work discipline have a significant effect on job satisfaction, leadership has a positive but not significant effect on job satisfaction, work ethic has a negative but not significant effect on performance, work discipline has a positive but not significant effect. significant effect on employee performance, leadership has a significant effect on employee performance, job satisfaction has a significant effect on employee performance. The results of indirect hypothesis testing show that the work ethic variable on employee performance through job satisfaction has a positive but not significant effect, work discipline on employee performance through job satisfaction has a positive but not significant effect and leadership on employee performance through job satisfaction has a positive but not significant effect.